PENINGKATAN KETERAMPILAN PROSES SAINS DAN MINAT BELAJAR MELALUI PEMBELAJARAN INKUIRI TERBIMBING BERBASIS PhET - Tri Wulan Mayliana; Hasan Subekti; Wahyu Budi Sabtiawan (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This research aimed to determine the improvement of students’ science process skills and students’ interest in learning through guided inquiry learning with PhET based media. The type of the research was one group pretest-posttest design and quantitative descriptive. The subject in this research were 20 students VII-D of Junior High School 28 Surabaya with 10 male students and 10 female students. The instruments in this research were test sheet and questionnaires. Data were collected by (1) pretest and posttest of science process skills (2) questionnaire of students’ interest in learning. The research results showed that there were improvement in students' process science skills consider as moderate category in N-Gain score and students' interest in learning from moderately to sufficient criteria. The students gave a positive response in learning implementation. Conclusion of this research was that the implementation of guided inquiry learning based on PhET media can improve the students’ science process skills and students' interest in learning.